Association Analysis on Recurrence of Bacterial Vaginosis Revealed Microbes and Clinical Variables Important for Treatment Outcome - Xiao, Bingbing; Wu, Chunyan; Song, Wenfeng; Niu, Xiaoxi; Qin, Nan; Liu, Zhaohui; Xu, Qian (Frontiers in Cellular and Infection Microbiology, 2019)
To investigate the parameters associated with post-treatment recurrence of bacterial vaginosis (BV), clinical factors and vaginal microbiota were examined and analyzed for BV patients who received standard metronidazole therapy. The variables associated with BV recurrence included clinical factors of past BV history, use of intravaginal device, and D7 Nugent score as well as many microbial genera, with Lactobacillus, Enterococcus, Ureaplasma, and Aerococcus being the top contributors. Co-occurrence network analysis showed that whereas overwhelming majority of interbacterial interactions were positive, negative interactions were present and connected mostly to Lactobacillus, Enterococcus, and to a less extent Ureaplasma, suggesting the importance of interbacterial antagonism for treatment outcome. The patients who were cured and recurrent also exhibited clear differences in the species composition of Lactobacillus: although L. iners remained the dominant species at all time points, L. crispatus, L. gasseri, and L. jensenii displayed apparent differences in relative abundance between the cure and recurrent groups. Based on these results, we developed a 5-component panel comprising Enterococcus, L. crispatus, Ureaplasma, Aerococcus, and L. jensenii for predicting recurrence using D7 data showed that it generated the specificity, sensitivity, and AUC values of 0.80, 0.66, and 0.73 for the discovery cohort and 0.80, 0.67, and 0.69 for the validation cohort. Our findings highlighted key microbial components for BV recurrence and suggested that they could be used to monitor the treatment outcome.